Building the Ridley Island coal terminal - Murray E. Blanchard; Charle Lawrence (Canadian Institute of Mining, Metallurgy and Petroleum, 1983)
"A significant addition to Canada's commodity export transportation capabilities is being built by Ridley Terminals Inc. on Ridley Island in the Port of Prince Rupert on British Columbia's north coast.Site preparation began in early 1982. By the end of 1983 the terminal will be receiving coal from two major new mines being developed in B. C.'s massive $2.5 billion northeast coal development.The RTI terminal will have initial capacity to transfer 12 million tonnes of coal a year from railcars to storage and to ships. Capacity will be doubled to 24 million tonnes as market opportunities are developed.The challenge of building this $220-million facility in less than 24 months, the benefits Canada has received from the work the project is generating, and the long-term faith in Canada that this project represents, are all part of the excitement which surrounds the Ridley Terminal and northeast coal developments.RIDLEY TERMINALS INC. (RTI) is building a very significant addition to Canada's commodity export transportation capabilities. The facility, on Ridley Island at Prince Rupert, on the north coast of British Columbia, is a key link in British Columbia's northeast coal development which in itself is a massive undertaking involving investment of some $2.5 billion. The entire project is making a substantial contribution to Canada's economy at a time when such contributions are sorely needed.The development is creating employment, not only in British Columbia where its various parts are being created by mining companies, railways and others, but also across the country where suppliers are manufacturing a wide variety of good s and equipment for the development's participants.The RTI terminal is no exception. It is a critical cog in this mega project's large transportation system and its construction is contributing substantially to job creation and to other economic activity, in the Prince Rupert area and in many other parts of British Columbia and the rest of Canada."